PENGARUH LAYANAN BIMBINGAN DAN KONSELING TERHADAP PRESTASI BELAJAR SISWA DI MA ULIN NUHA LUBUKLINGGAU - Aini, Jannatun; Nurmal, Ifnaldi; Wahyudi, Edi (MUHAFADZAH: Jurnal Ilmiah Bimbingan dan Konseling Islam, 2024)
In undergoing the learning process students neet help and guidance of others. the teachers in all the teachings given effectively implied a form of guidance. in the process of education and teaching of students can not be separated from the problem, this can be anticipated through learning guedance and counseling in order to foster student achievement that receives low learning outcomes. student learning achievement must be improved in order to obtain maximum learning results. this lack of learning achievement is a problem that has plagued many students at school in general. The purpose of this study was to prove the presence or absence of the influence of tutoring and learning counseling on the learning achievement of eleven grade students of Lubuklinggau. in this case the hypothesis there is a significant influence of learning guidance and counseling on student learning achievement. so ho was refused and ha was accepted. then there is an influence between guidance and learning counseling on learning achievement of XI grade students MA Lubuklinggau is 0.013 < 0.05. at the error level of 5% Siswa memerlukan bantuan dan bimbingan orang lain selama proses pembelajaran. Secara efektif, guru menyiratkan bimbingan dalam proses pendidikan dan pengajaran siswa tidak lepas dari masalah. Hal ini dapat diantisipasi melalui bimbingan dan konseling untuk meningkatkan prestasi siswa dengan hasil belajar rendah. Untuk memaksimalkan hasil belajar, prestasi belajar siswa harus ditingkatkan. Banyak siswa di sekolah menghadapi masalah kurangnya prestasi belajar ini. Tujuan penelitian ini adalah untuk membuktikan ada tidaknya pengaruh bimbingan belajar dan konseling pembelajaran terhadap prestasi belajar siswa kelas XI Lubuklinggau. dalam hal ini hipotesisnya terdapat pengaruh signifikan pembelajaran bimbingan dan konseling terhadap prestasi belajar siswa. jadi ho ditolak dan ha diterima. maka terdapat pengaruh antara bimbingan dan pembelajaran konseling terhadap prestasi belajar siswa kelas XI MA Lubuklinggau adalah 0,013 < 0,05. pada tingkat kesalahan 5%